STUDI FENOMENOLOGI : EFEKTIVITAS CO-BRANDING DAN FANATISME SEBAGAI STRATEGI PEMASARAN MCDONALD’S PADA BTS MEALS - Nurcholis, Muhamad; Hakimah, Ema Nurzainul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
In 2021 McDonald's will be in the spotlight in Indonesia for collaborating with the international boy group BTS and as a result of this collaboration, McDonald's and BTS released a limited edition menu, namely BTS Meals. High buying interest from fans caused a stir so queues of buyers created a crowd in the midst of the COVID-19 pandemic which had an impact on the temporary closure of several McDonald's outlets in Indonesia. This study aims to determine the effectiveness of co-branding and fanaticism used by McDonald's as a marketing strategy on the BTS Meals collaboration menu. This research is a qualitative research using a phenomenological approach. The determination of informants in this study uses 5 criteria, including relevance, recommendation, rapport, readiness, and reassurance (5R). Furthermore, interviews were carried out in-depth with several ARMY or BTS fans. The results of the study show that fanaticism is the main factor in causing consumer purchase motives on the BTS Meals menu.